ASPECTOS EPIDEMIOLÓGICOS DA INFECÇÃO POR M. TUBERCULOSIS EM MATO GROSSO DO SUL, 2016 A 2020. - Cleide Aparecida Alves Souza (2022)
Mycobacterium tuberculosis (ITB) infection is considered, when the individual comes into contact with the bacillus from an individual with pulmonary or laryngeal tuberculosis (TB). The bacillus remains viable without causing tuberculosis disease (DTB), but reactivation can occur if the individual has conditions that favor cell multiplication, such as in immunosuppressed patients, with comorbidities or in immunosuppressive therapy. Preventive treatment by M. tuberculosis (TPT) infection, at high risk of developing DTB, is part of TB resolution strategies. This study, accomplished in Mato Grosso do Sul, describes the epidemiology of TBI, from 2016 to 2020. Cross-sectional, descriptive study with an analytical component, covering 79 municipalities in the state using secondary data from SINAN; LABGERENCIAL; IL-TB and physical notification forms (FN-TBI) for the period and/or municipalities without IL-TB implementation. The data were organized and processed with the Microsoft Excel-2016 program, “R” language and QGIS geoprocessing tool. The analyzes comprised descriptive and inferential statistics with a 95% confidence interval (95%CI) for sociodemographic proportions and odds ratios for the outcome estimate of Logit-type modeling and a significance level of p<0.05. The study was approved by the Research Ethics Committee of the Federal University of Mato Grosso do Sul, CAAE: 30719320.0.0000.0021. 968 people were included in TPT, with 773 (3.97% - CI [3.69%; 4.25%]) coming from DTB contacts, which resulted in a higher proportion of treated among contacts without laboratory confirmation than those contacts with laboratory confirmation (102 (4.00% - CI [3.29%; 4.86%], 491 (3.01% - CI [2.76%; 3.29%]) respectively). Other 195 related to individuals with no history of contact, including 32 PLHIV representing less than 5% of PLHIV with CD4 ≤ 350 cells/mm³ 32/741 (4.31%). Compared to age groups, the concentration was between 11 and 20 years old (CI 95% = 18.90 (16.51; 21.55), with a predominance of females (CI 95% = 53.31 (50.10; 56.48) and indigenous people (43.18%, CI95 %:40.04-46.37. With the implementation of IL-TB, there was an increase in notifying municipalities (13 to 50) and in people notified in TPT (147%), municipalities with TB patients with laboratory confirmation showed a contact ratio registered (5.15) higher than the statistical data of residents per household. and consonance of the TB exclusion exams and TBI indication with the protocol criteria in 88.50% of the individuals who underwent all the exams. Correlating treatment with rifampicin and isoniazid, rifampicin showed better performance in the number of doses taken (80%). The frequency of completion of complete treatment was significantly higher among the indigenous population and in those individuals, who underwent all examinations. It concludes gaps in treatment indications, mainly among TB contacts and strengthening of TPT indication in priority groups. The implementation of the IL-TB proved to be effective in terms of expanding the number of reported, monitored and treated TBIs.